Light‐Responsive Programmable Shape‐Memory Soft Actuator Based on Liquid Crystalline Polymer/Polyurethane Network. (27th January 2023) - Song, Chenjie; Zhang, Yuhan; Bao, Jinying; Wang, Zizheng; Zhang, Lanying; Sun, Jian; Lan, Ruochen; Yu, Zhan; Zhu, Siquan; Yang, Huai
Abstract: Liquid crystalline polymers (LCPs), especially liquid crystalline elastomers (LCEs) can generate ultrahigh shape change amplitude but has lower mechanical strength. Although some attempts have been tried to improve the mechanical performance of LCE, there are still limitations including complicated fabrication and high actuation temperature. Here, a versatile method is reported to fabricate light‐driven actuator by covalently cross‐linking polyurethane (PU) into LCP networks (PULCN). This new scheme is distinct from the previous interpenetrating network strategy, the hydrogen bonds and covalent bonds are used in this study to improve the miscibility of non‐liquid‐crystalline PU and LCP materials and enhance the stability of the composite system. This material not only possesses the shape memory properties of PU but shows shape‐changing behavior of LCPs. With a shrinkage ratio of 20% at the phase transition temperature, the prepared materials reached a maximum mechanical strength of 20 MPa, higher than conventional LCP. Meanwhile, the resulting film shows diverse and programmable initial shapes by constructing crosslinking density gradient across the thickness of the film. By integration of PULCN with near‐infrared light‐responsive polydopamine, local and sequential light control is achieved. This study may provide a new route for the fabrication of programmable and mechanically robust light‐driven soft actuator. Abstract : A light‐driven shape memory liquid crystalline network film by covalently cross‐linking polyurethane into liquid crystalline polymer networks (PULCN) is realized. The all‐optically controlled novel PULCN material enabled the fabrication of artificial muscles and biomimetic devices.